Coupled analysis on the thickness-shear vibrations of a quartz plate resonator covered with micro-beams immersed in inviscid liquid and computation of the induced frequency-shift by the surface loadings. Issue 7 (2nd July 2016) - Xie, Xuan; Kong, Lingcheng; Zhang, Jun; Wang, Yuxi; Hu, Yuantai; Chen, Xuedong
ABSTRACT: The dynamic equations of a quartz crystal resonator (QCR) vibrating in the thickness-shear modes (TSM) with the upper surface covered by an array of micro-beams, while the micro-beams are immersed in inviscid liquid, is established. A frequency-dependent effective mass ratio is put forward to simulate the effect of surface loadings (micro-beams immersed in liquid) on the dynamic characteristics of QCR. The seeping depth of vibration energy into liquid is analyzed and the added mass of liquid to micro-beams is examined. The induced frequency-shift of the compound QCR system consisting of QCR and the surface loadings is calculated in detail.